The Influence of Creativity and Innovation on Business Success - Putri Mauliza (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to find out whether Creativity and Innovation affect the Business Success of PT Abdya Centra Perabot. The research methodology used is descriptive quantitative method. The population in this study were all PT customers as many as 80 respondents in the city of Medan, so the number of samples used by researchers was 80 customers. Data were analyzed using multiple linear regression analysis method. The results showed that Creativity and Innovation had a positive and significant effect on Business Success at PT Abdya Centra Perabot. The results of this study are supported by the value of R square (R2) = 0.806 or 80.6%, which means that Creativity and Innovation simultaneously have an influence of 80.6% on Business Success at PT Abdya Centra Perabot. While the remaining 19.4% is influenced by other factors originating from outside this research model such as perceived value, service quality, price, segmentation, targeting and positioning. The purpose of this study is to determine the effect of Personal Selling, Sales Promotion and Brand Equity on Sales Volume at PT. Uni Diesel.